Age-dependent QTL affecting body weight in gilthead seabream (Sparus aurata L.) - LOUKOVITIS, D.; CHATZIPLIS, D.; BATARGIAS, C. (Mediterranean Marine Science, 2016)
<!–[if gte mso 9]> Normal 0 false false false EL X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> We examined 24 maternal half-sib families of gilthead seabream to identify quantitative trait loci (QTL) associated with body weight at four time points during a production cycle. 57 brooders and 637 offspring were genotyped for 14 informative microsatellite markers, spanning linkage groups 1 and 21. The QTL detection method was based on half-sib interval mapping analysis through a linear regression approach. One QTL was found significant at all time points in linkage group 1, with its effect having different profile across time, and one QTL in linkage group 21 that seems to impact body weight at a later growth stage of the species. Current results verified previously published QTL for growth in the above linkage groups, using a different genetic background of seabream. These QTL can be considered as valuable candidates for use in marker-assisted selective breeding programs, aiming at high rates of genetic improvement for growth in S. aurata. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>